Profiles of mood state fatigue scale is responsive to fatiguing protocol but shows no relationship to perceived or performance decrements. Issue 3 (3rd February 2019) - Johnson, Caleb D.; Beethe, Anne Z.; Eagle, Shawn R.; Mi, Qi; Lovalekar, Mita T.; Pepping, Gert‐Jan; Nindl, Bradley C.; Flanagan, Shawn D.; Connaboy, Christopher
Abstract : The Profiles of Mood State, fatigue subscale (POMS‐Fatigue) has been proposed as a measure of fatigue during exercise. No previous research has established whether it is responsive to fatiguing exercise or correlated with measures of fatigability. Twenty‐three participants performed an incremental, fatiguing bout of exercise on a treadmill (Mean time ≈ 55 minutes). Measures of fatigability included: ratings of perceived exertion (RPE), heart rate, rate of force development, perceptual‐motor reaction times, and maximal jump distance. The POMS‐Fatigue and fatigability measures were assessed pre‐ and post‐exercise. Maximal scores and pre‐post change scores for the POMS were calculated to assess responsiveness and correlation coefficients were calculated to assess the relationship with fatigability measures ( α = 0.05). The POMS‐Fatigue (0‐20) showed good responsiveness, with a mean change of 16.26 points (95% CI = 15.18‐17.34), with every participant demonstrating a change of at least 11 points. The strongest correlations between POMS‐Fatigue change and max scores were with maximal RPE ( R = 0.251‐0.376); however, no correlations showed statistical significance. In summary, the POMS‐Fatigue was responsive to fatiguing exercise. However, the lack of a relationship with fatigability measures may point toward the need for refinement of several items on the scale.